Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Why the tensor product of graded algebras is defined with a commutation $\epsilon $ like this : $(a\otimes b)(c\otimes d)= \epsilon(ac\otimes bd)$ ? what is the usefulness of the commutator $\epsilon$ here ? why that tensor product is not defined simply by $(a\otimes b)(c\otimes d)= (ac\otimes bd)$ ?

share|cite|improve this question
Where did you get this definition? I have never seen the tensor product of algebras defined with that element. I even double checked: Maybe for clarity you should add something like: "I have two $R$-algebras $A$ and $B$, etc..." – acyrl Sep 26 '12 at 9:49
see Bourbaki, Algebras chapters 1 to 4 – Albert_T Sep 26 '12 at 10:04
Sorry, I had missed the graded bit. – acyrl Sep 26 '12 at 11:16
Even taking into account superalgebras and the Koszul sign rule, I don't think $(a\otimes b)(c\otimes d)= \epsilon(ac\otimes bd)$ is anywhere near the correct formula. – darij grinberg Oct 8 '15 at 0:27

The use of the $\epsilon$ here can be to inherit structure from $A$ and $B$: If $A$ and $B$ are for example graded anticommutative algebras, and you want $A \otimes_R B$ to be graded anticommutative also, $(a \otimes b)(c \otimes d) = (ac \otimes bd)$ won't do: Say for example $a \in A_0$, $c \in A_1$, $b \in B_1$, $d \in B_0$. The you have $ac = ca$, $bd = db$ and hence \[ (a \otimes b)(c \otimes d) = (ac \otimes bd) = (ca \otimes db) = (c \otimes d)(a \otimes b) \] But if we want $A \otimes B$ to be graded anticommutative, we need a $-$ here, as $a \otimes b$, $c \otimes d \in (A\otimes B)_1$.

If we instead define \[ (a \otimes c)(b \otimes d) = (-1)^{\deg b\deg c} (ab \otimes cd) \] for homogeneous $b$ and $c$, the above example with $\deg a = \deg d = 0$, $\deg b = \deg c = 1$ gives \[ (a \otimes b)(c \otimes d) = (-1)^{1 \times 1}(ac \otimes bd) = -(ca \otimes db) = -(-1)^{0\times 0}(c \otimes d)(a \otimes b) = -(c\otimes d)(a \otimes b) \] as wished.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.